Some Features of Nighttime D and E Region Electron Density Profiles in the Polar Ionosphere - Miyazaki, Shigeru; Ogawa, Tadahiko; Mori, Hirotaka (1981)
P(論文) The empirical formulae are deduced to infer the nighttime electron density during auroral disturbances from the 30MHz CNA and geomagnetic disturbance levels. The results indicate that log N_e=-1.18×(10)^<-3>⊿H+4.84 at 105km and log N_e=0.362x+4.12 at 90km where N_e is the electron density in (cm)^<-3>, ⊿H is the variation of geomagnetic horizontal component in nT and x is the 30MHz CNA level in dB. departmental bulletin paper